Anthropology of Pain in Gina Pane’s Performances: From Sacred Tradition to Provocation - Berest, Valeria A. (Actual Problems of Theory and History of Art, 2025)
Gina Pane is one of the first representatives of the so-called “body art” in France. The mainsubjects of her performances are pain and different body injuries. The concept of pain has been reflected inart throughout the centuries: from images of suffering on the medieval frescoes to a radical performance of the 20th century, expanding the boundaries of the human body. The phenomenon of pain is complex andusually analyzed within the context of medical practices. According to German philosopher Dietmar Kamper, pain and suffering are becoming the new experience allowing to restore the functions of the imagination and expand the experience of perception and reflection of the reality. For Gina Pane, pain is the means of social and political statement, an indispensable element of self-sacrifice in the name of the Other. Her artistic practice is intentional, and the subject of this is the generalized figure of the Other. It builds a special figurative system in which the motive of the Saint, who experiences a special state of purification through the prism of bodily suffering in the name of the Other, becomes fundamental. Performance is the only possible medium that can transfer the pain into the visible and the sensory forms. The artist’s body becomes the referent of the experienceof pain. Performance integrates pain into reality, facilitating the acceptance of trauma and suffering. Much of Gina Pane’s works are based on biblical stories, saints’ and martyrs’ vitae. The motif of the cross and the suffering body of the martyr form a series of references and signs characterizing her artistic language. In her artistic practices, Gina Pan balances between the possibilities of performance and the embodiment of the phenomenological body of the artist and the possibilities of visual representation of the key aspects ofthe performance act itself, where the material embodiment — photographic images with a clearly aligned vision — becomes an independent element of influence and manipulation.